Shaping the phycosphere Analysis of the EPS in diatom-bacterial co-cultures - Daly, Giulia (Journal of phycology, 2023)
© 2023 The Authors. Journal of Phycology published by Wiley Periodicals LLC on behalf of Phycological Society of America.